2010
DOI: 10.1152/japplphysiol.00423.2009
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of the cough reflex by exercise and voluntary isocapnic hyperpnea

Abstract: Little is known about the effects of exercise on the sensory and cognitive aspects of coughing evoked by inhalation of tussigenic agents. The threshold for the cough reflex induced by inhalation of increasing nebulizer outputs of ultrasonically nebulized distilled water (fog), an index of cough reflex sensitivity, was assessed in twelve healthy humans in control conditions, during exercise and during voluntary isocapnic hyperpnea (VIH) at the same ventilatory level as the exercise. The intensity of the urge to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 59 publications
(92 reference statements)
4
42
0
Order By: Relevance
“…The urge to cough is associated with widespread activation of cortical and subcortical structures (179). Hypoxia, exercise, and voluntary hyperventilation also suppress coughing (72,165). It is clear from this description that the cough CPG integrates inputs from a variety of reflex and nonreflex sources and adapts or captures neurons involved in eupnea for use in an augmented inspiratory and expiratory effort aimed at cleansing the airways.…”
Section: Coughing and Sneezingmentioning
confidence: 99%
“…The urge to cough is associated with widespread activation of cortical and subcortical structures (179). Hypoxia, exercise, and voluntary hyperventilation also suppress coughing (72,165). It is clear from this description that the cough CPG integrates inputs from a variety of reflex and nonreflex sources and adapts or captures neurons involved in eupnea for use in an augmented inspiratory and expiratory effort aimed at cleansing the airways.…”
Section: Coughing and Sneezingmentioning
confidence: 99%
“…Pharyngeal afferents can activate not only the gag reflex (Bassi et al, 2004), but also coughing or the "urge-to-cough"; the receptors implicated are probably innervated by vagal and glossopharyngeal nerves or by trigeminal branches . Central and peripheral mechanisms involved in exercise and voluntary isocapnic hyperventilation may downregulate the cough response (Lavorini et al, 2010;Poussel et al, 2014). However, exercise (electrically induced hindlimb muscular contractions) in ovalbumin-sensitized rabbits fails to produce similar effects (Tiotiu et al, 2017).…”
Section: Neuronal Recordings C-fos Immunohistochemistry and Lesion Ementioning
confidence: 99%
“…(2, 3) However, some clinicians have observed that exercise can exacerbate cough in any child with a pre-existing cough, irrespective of diagnosis. Yet, in adult studies on cough sensitivity to fog (which is dependent on minute volume), desensitization of the cough reflex occurs post-exercise (4). Increased cough is usually associated with increased cough reflex sensitivity.…”
Section: Introductionmentioning
confidence: 99%